Long-term neuropsychiatric outcomes after pallidal stimulation in primary and secondary dystonia. (4th August 2015) - Meoni, Sara; Zurowski, Mateusz; Lozano, Andres M.; Hodaie, Mojgan; Poon, Yu-Yan; Fallis, Melanie; Voon, Valerie; Moro, Elena
Abstract : Objective: To evaluate changes in the diagnosis of Axis I psychiatric disorders in patients with primary and secondary dystonia after deep brain stimulation (DBS) of the globus pallidus internus (GPi). Methods: Structured Clinical Interviews for the DSM-IV, Axis I psychiatric disorders, were prospectively performed before and after surgery. Diagnoses were made based on DSM-IV criteria. Psychiatric disorders were grouped into 5 categories: mood, anxiety, addiction, obsessive-compulsive disorders, and psychosis. Patients could be stratified to more than one category. Rates for unchanged diagnoses, diagnoses in remission, and new-onset diagnoses after surgery for each category were calculated. Results: Fifty-seven patients with primary and secondary dystonia were included. Mean ± SD age at surgery and dystonia duration at time of surgery was 50.6 ± 13.8 and 19.0 ± 13.2 years, respectively. Preoperatively, 37 Axis I diagnoses were made in 25 patients, 43.8% of those presenting with at least 1 Axis I diagnosis (mostly mood and anxiety disorders). Mean ± SD duration of psychiatric follow-up was 24.4 ± 19.6 months. Overall, after surgery no significant changes ( p = 0.16) were found in Axis I diagnoses (23 patients, 40.3%): 27 (73%) unchanged, 10 (27%) in complete remission, and 4 (12.9%) new-onset diagnoses. Conclusions: Our results support the overall psychiatric stability of patients with primary and secondary dystonia treated with GPi DBS. However, considering the high psychiatric morbidity in the dystonia population, psychiatric assessments before and after surgery are strongly recommended. Classification of evidence: This study provides Class IV evidence that GPi DBS does not change Axis I psychiatric diagnoses in patients with primary and secondary dystonia.